PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS CABAI RAWIT (Capsicum frutescens L.) YANG DITANAM DI LUAR MUSIM DENGAN PERLAKUAN PUPUK KANDANG PLUS - Fathi, Hidayatul; Jaya, I Komang Damar; Sudika, I Wayan (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
Cayenne pepper is one of the horticultural commodities that its production is low in the rainy season (off-season) due to the high potential for flower abortion and plant disease attacks. This study aimed to determine the effect of manure plus and varieties on the growth and yield of some cayenne pepper varieties planted off- season. The experiment was carried out in the 2020/2021 rainy season in Gumantar Village, Kayangan District, North Lombok Regency. The treatments were arranged using a Split Plot design with three replications. The main plot was manure treatment with 2 treatment levels, with and without manure plus, while as sub-plots were varieties, Taruna, Sret and Mutiara Bumi. The results showed that plant height and number of leaves at the age of 56 DAP and 98 DAP were significantly affected by manure plus treatment, and by variety too. The effect of varietal treatment showed significantly different on yield variables, such as fruit weight per plant and fruit weight per plot. The highest yield was shown by Taruna variety while Sret and Mutiara Bumi varieties did not show different results. There was an interaction between the treatment of manure and variety on the variable number of flowers, number of fruits and percentage of flower abortion. The best interaction effect occurred in the treatment of Taruna variety treated with manure plus. From the results of this study, it can be suggested to grow Taruna variety treated with manure plus to obtain high yields of cayenne pepper grown off-season on drylands.